Reaction kinetics of liquid phase air oxidation of p-cresol to p-hydroxybenzaldehyde - Kshirsagar, V. S.; Nadgeri, J. M.; Tayade, P. R.; Rode, C. V. (Applied Catalysis A-General, 2008)
The kinetics of liquid phase oxidation of p-cresol to p-hydroxybenzaldehyde has been investigated using insoluble cobalt oxide (CO3O4) catalyst at oxygen partial pressures in the range 0.1-1.5 MPa, reaction temperatures 333-393 K, p-cresol concentrations 0.49-1.53 kmol/m(3) and catalyst loadings 0.38-3.03 kg/m(3). The effects of oxygen partial pressure, reaction temperature, p-cresol concentration and catalyst loading on the initial rate of reaction have been studied. The initial rate varied linearly with catalyst loading up to 1.5 kg/m(3) beyond which it was independent of the catalyst loading while first-order dependence was observed with variation in oxygen partial pressure. A rate expression has been proposed considering Langmuir-Hinshelwood (LH) type mechanism, based on the initial rate data. A batch reactor model was also developed based on the kinetics studied and the concentration time profile predicted by the model was in good agreement with the experimental data. The activation energy for the liquid phase oxidation of p-cresol was found to be 39.6 kJ/mol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Co3O4; kinetics; p-cresol oxidation; XPS; XRD

Characterization of clay intercalated cobalt-salen catalysts for the oxidation of p-cresol - Kshirsagar, V. S.; Garade, Ajit C.; Mane, R. B.; Patil, K. R.; Yamaguchi, A.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2009)
The intercalation of cobalt-salen complexes into the interlamelar spaces of montmorillonite clay was investigated by various characterization studies. The ``neat'' cobalt-salen complex showed a weight loss at 368 degrees C while the weight loss for the corresponding intercalated complex was observed at much higher temperature of 492 degrees C due to decomposition of the complex. The thermal stabilization observed was due to the host-guest interaction of clay and metal complex and thus confirmed the intercalation. The XANES spectrum of Co(salen)-mont sample revealed the change of symmetry from the tetrahedral in plane to the octahedral structure having an axial bonding of oxygen to the cobalt, indicating that cobalt atoms in Co(salen)-mont were coordinated axially with the lattice oxygen of montmorillonite. Both XANES and EXAFS results indicated that cobalt atoms in Co(salen)-mont form two additional Co-O bonds with a bond length of 0.199 nm by the intercalation while retaining the Co-salen structure. Co-salen intercalated into the montmorillonite clay showed the highest activity for the air oxidation of p-cresol, giving 88% selectivity to the oxidation products. Effects of NaOH concentration and various solvents on the conversion and selectivity patterns also have been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cobalt-oxygen bond; Cobalt-salen; Extended X-ray absorption fine structure; Intercalation; Lattice oxygen; Montmorillonite; X-ray absorption near edge structure

Selective hydroxyalkylation of phenol to bisphenol F over dodecatungstophosphoric acid (DTP) impregnated on fumed silica - Garade, Ajit C.; Kshirsagar, V. S.; Rode, C. V. (Applied Catalysis A-General, 2009)
The catalyst activity of various solid acids, such as fumed Silica (SiO(2)) dodecatungstophosphoric acid (DTP), DTP impregnated on SiO(2), amberlyst-15 and montmorillonite KSF/0, was studied for the hydroxyalkylation of phenol to bisphenol F. A well-dispersed DTP on SiO2 catalyst was prepared by the wet impregnation method. The effect of DTP loading on SiO(2) was also compared with bulk DTP and other solid acid catalysts. 20% DTP/SiO(2) catalyst gave the highest products yield of 34.2% and selectivity of 90.1% to bisphenol F, at 353 K and with a phenol-to-formaldehyde mole ratio of 5:1. Ammonia TPD studies of various catalysts showed that an appropriate combination of both strong and weak acid sites of DTP/SiO(2) Was mainly responsible, rather than only the stronger acidity of bulk DTP, for its highest catalytic activity and selectivity. The effect of various reaction parameters like mole ratio, catalyst concentration, temperature and reaction time on product yield and bisphenol F selectivity was also investigated. The catalyst recycle was established by catalyst activity testing. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Bisphenol F; Hydroxyalkylation; NH(3)-TPD; Reaction pathways; solid acid catalysts

Acidity tuning of montmorillonite K10 by impregnation with dodecatungstophosphoric acid and hydroxyalkylation of phenol - Garade, Ajit C.; Kshirsagar, V. S.; Mane, R. B.; Ghalwadkar, Ajay A.; Joshi, U. D.; Rode, C. V. (Applied Clay Science, 2010)
Acidity tuning of montmorillonite K10 (mont K10) was achieved by impregnating with dodecatungstophosphoric acid (DTP). The effect on the hydroxyalkylation of phenol was studied at 353 K with phenol to formaldehyde molar ratio of 5. The nature and strength of acid sites were determined by NH(3)-TPD measurement while the distribution of Brensted and Lewis acid sites expressed as B/L ratio, was determined by pyridine IR technique. Among various loadings of DTP (5-60%) studied for the hydroxyalkylation of phenol, 20% DTP/mont K10 showed the highest catalyst activity (90% selectivity to bisphenol F with 28% conversion of phenol). Both total concentration of acid sites and the distribution of acid sites in a high temperature region were required for the high bisphenol F selectivity. Our catalyst (20% DTP/Mont K10) could be recycled three times. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acidity tuning; Dodecatungstophosphoric acid/Montmorillonite K10; Hydroxyalkylation; Impregnation; Temperature programmed desorption

Structure-activity studies of dodecatungstophosphoric acid impregnated bentonite clay catalyst in hydroxyalkylation of p-cresol - Garade, Ajit C.; Kshirsagar, V. S.; Jha, Ajay; Rode, C. V. (Catalysis Communications, 2010)
Bentonite clay impregnated with dodecatungstophosphoric acid (20% DTP/BNT) showed an excellent activity, selectivity and stability [95% product yield with 94% selectivity to 2, 2'-methylenebis (4-methylphenol), DAM] for the hydroxyalkylation of p-cresol with formaldehyde at 353 K and for a mole ratio of 5. Ammonia-TPD results showed that an increase in total concentration of acid sites from 4.9 of parent bentonite to 11.6 micromoles per surface area NH(3) (mu molS(-1) NH(3)) of 20% DTP/BNT was due to a strong interaction of protons of bulk DTP with surface hydroxyl groups of BNT as evidenced by (31)P NMR studies. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: (31)P CPMAS NMR; Bentonite; Hydroxyalkylation; p-Cresol; surface modification

Liquid phase oxidation of p-vanillyl alcohol over synthetic Co-saponite catalyst - Garade, Ajit C.; Biradar, Narayan S.; Joshi, S. M.; Kshirsagar, V. S.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Applied Clay Science, 2011)
Effect of cobalt loading on porosity of synthetic Co-saponite catalysts and on the air oxidation of p-vanillyl alcohol was studied by varying Co content in the range of 5% to 30% using in situ precipitation method. The pore size increased from 1.29 to 3.69 nm indicating a transition from micro to meso porosity, with increase in Co loading from 5% to 30%. The distribution ratio of Co(3)O(4)/CoO phases as estimated from TPR studies, also increased from 0.84 to 1.67 with increase in Co loading from 5% to 13% and remained almost constant (1.7) with further increase in Co loading up to 30%. The highest activity (conversion 55%) and selectivity of 99% to p-vanillin obtained for 13% Co-saponite in p-vanillyl alcohol oxidation was due to the highest distribution ratios of Co(3)O(4)/CoO phases. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Co-saponite; Cobalt oxide phase ratio; p-Vanillin; p-Vanillyl alcohol oxidation; Porosity transition; Temperature programmed reduction

Reply to the comments of vicente et al. on ``liquid phase oxidation of p-vanillyl alcohol over synthetic co-saponite catalyst'' applied clay science (2010), doi:10.1016/j.clay.2010.10.026 - Rode, Chandrashekhar V.; Garade, Ajit C.; Biradar, Narayan S.; Kshirsagar, V. S. (Applied Clay Science, 2011)